Investigating the relationship between C677T polymorphism of the Methylenetetrahydrofolate Reductase Gene and the levels of homocysteine in primary and secondary infertile women in Isfahan - Elham Sonbolestan; Hossein Sazgar; Noosha Zia-Jahromi; Farzaneh Mohammadi Farsani (Fasa University of Medical Sciences, 2018)
Background & Objectives: Methylene Tetrahydrofolate Reductase (MTHFR) gene, as an important genetic factor affecting infertility, encodes Methyl Dihydrofolate Reductase enzyme which helps to regulate the levels of homocysteine in the body. Mutations in this gene can reduce the activity of the enzyme, which leads to increase levels of blood homocysteine and may cause infertility. The purpose of this research was to investigate the relationship between C677T polymorphism of MTHFR gene and infertility. Material & Methods: In this study, 100 samples from infertile and fertile women with a history of abortion and 100 healthy pregnant were selected. After extracting the DNA from peripheral blood, the genotype of the samples was analyzed by PCR-RFLP method. SPSS software was also used to investigate the relationship between C677T polymorphism and infertility (using t. test, Chi-square test and logistic regression). Results: C677T polymorphism of MTHFR gene, resulted in a significant increase in the level of homocysteine and decrease levels of folate and vitamin B12 in homozygous women. However, there was not any relationship between the genotype of heterozygous patients with the level of homocysteine, folate and vitamin B12. Conclusion: C677T polymorphism of MTHFR gene may be associated with the increased levels of homocysteine and decreased levels of folic acid and vitamin B12 in the body, which can cause fetus recurrent miscarriage syndrome.